2018
DOI: 10.1186/s12917-018-1736-1
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a broadly reactive reverse transcription recombinase polymerase amplification assay for rapid detection of murine norovirus

Abstract: BackgroundMurine norovirus (MNV) is recognized as the most prevalent viral pathogen in captive mouse colonies. The rapid detection assay for MNV would be a useful tool for monitoring and preventing MNV infection. A recombinase polymerase amplification (RPA) assay was established in this study to provide a solution for rapid and sensitive detection of MNV.ResultsThe detection limit of the RT-RPA assay for the detection of MNV was 1 × 102 copies of RNA molecules per reaction. The assay was specific since there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
1
18
1
Order By: Relevance
“…The sensitivity of the RT-RPA assay was evaluated by the above method. The result showed that the assay could detect 10 2 copies ARV strain GX110058 and ARV strain B-98 S1 molecules, respectively (Supplementary Figures 7, 8), confirming that several point mutations have little effect on the sensitivity of the RT-RPA assay which was reported previously (21).…”
Section: Detection Limit Of the Assaysupporting
confidence: 86%
See 2 more Smart Citations
“…The sensitivity of the RT-RPA assay was evaluated by the above method. The result showed that the assay could detect 10 2 copies ARV strain GX110058 and ARV strain B-98 S1 molecules, respectively (Supplementary Figures 7, 8), confirming that several point mutations have little effect on the sensitivity of the RT-RPA assay which was reported previously (21).…”
Section: Detection Limit Of the Assaysupporting
confidence: 86%
“…Although RPA method was a latterly invented technique, it has attracted much attention for the last few years (19). RPA reaction was initiated by three proteins, including a recombinase, a strand-displacing DNA polymerase and a singlestranded DNA-binding protein at a single optimum temperature between 37 and 42 • C. Accumulating studies demonstrates that RPA technique has been successfully used in rapid detection of bacteria, viruses, and parasites (20)(21)(22)(23)(24). Endpoint detection of RPA products could be carried out by nucleic acid electrophoresis and lateral flow dipstick (LFD) (25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the analytical sensitivity of the PDCoV RT‐RPA assay was 100 copies molecules, which was 10‐fold lower sensitivity compared with RT‐qPCR (Ma, Zeng, Cong, et al., ). The relative low sensitivity of the RT‐RPA assay was confirmed by the results of intestine samples, in which one sample containing low RNA titre (55 RNA copies) was tested negative by RT‐RPA.…”
Section: Discussionmentioning
confidence: 53%
“…Linear regression analysis showed a poor correlation between TT values and C T values (Figure b), implying the RT‐RPA assay could not be used to quantitative detection of PDCoV. To confirm the results of RT‐RPA, amplicons of 20 positive samples were obtained by conventional RT‐PCR (Ma, Zeng, Cong, et al., ) and sequenced. The generated sequences were 99% identical to that of N gene of PDCoV (data not shown).…”
Section: Resultsmentioning
confidence: 99%